2009
DOI: 10.1093/brain/awp136
|View full text |Cite
|
Sign up to set email alerts
|

The pattern and diagnostic criteria of sensory neuronopathy: a case-control study

Abstract: Acquired sensory neuronopathies encompass a group of paraneoplastic, dysimmune, toxic or idiopathic disorders characterized by degeneration of peripheral sensory neurons in dorsal root ganglia. As dorsal root ganglia cannot easily be explored, the clinical diagnosis of these disorders may be difficult. The question as to whether there exists a common clinical pattern of sensory neuronopathies, allowing the establishment of validated and easy-to-use diagnostic criteria, has not yet been addressed. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
182
0
7

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 218 publications
(197 citation statements)
references
References 41 publications
8
182
0
7
Order By: Relevance
“…The asymmetry in the neurophysiological findings is not included in the published diagnostic criteria (Camdessanché et al., 2009), but the criteria only include the clinical asymmetric sensory deficits.A diagnosis of SG can still be made even in the absence of values below normal limits, as the diagnosis is based on the number asymmetries (often patients with SG at early stages present with asymmetric SNAPs, which are still within normal limits). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The asymmetry in the neurophysiological findings is not included in the published diagnostic criteria (Camdessanché et al., 2009), but the criteria only include the clinical asymmetric sensory deficits.A diagnosis of SG can still be made even in the absence of values below normal limits, as the diagnosis is based on the number asymmetries (often patients with SG at early stages present with asymmetric SNAPs, which are still within normal limits). …”
Section: Discussionmentioning
confidence: 99%
“…The asymmetry in the neurophysiological findings is not included in the published diagnostic criteria (Camdessanché et al., 2009), but the criteria only include the clinical asymmetric sensory deficits.…”
Section: Discussionmentioning
confidence: 99%
“…Camdessanché et al investigated whether SNAP amplitudes of the median, ulnar, radial, sural and superficial peroneal nerves would individually enable the distinction between GNP and PNP 3 . They found that nerves in the upper limbs are significantly more compromised in GNP, but using different thresholds to separate GNP and PNP sensitivity and specificity values ranged between 70 and 85% 3 .…”
Section: Discussionmentioning
confidence: 99%
“…They found that nerves in the upper limbs are significantly more compromised in GNP, but using different thresholds to separate GNP and PNP sensitivity and specificity values ranged between 70 and 85% 3 . This motivated us to investigate other parameters derived from NCS that might work better.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were diagnosed with sensory ganglionopathy when only sensory fibers were affected in an asymmetrical fashion or where no sensory responses were elicited by any sensory nerve with motor responses being normal [11]. Finally, patients with involvement of sensory and motor fibers of specific nerves, sparing others, were diagnosed with mononeuritis multiplex.…”
Section: Methodsmentioning
confidence: 99%